Stem Cell Spheroids: Switchable Water‐Adhesive, Superhydrophobic Palladium‐Layered Silicon Nanowires Potentiate the Angiogenic Efficacy of Human Stem Cell Spheroids (Adv. Mater. 41/2014). (November 2014) - Seo, Jungmok; Lee, Jung Seung; Lee, Kihong; Kim, Dayeong; Yang, Kisuk; Shin, Sera; Mahata, Chandreswar; Jung, Hwae Bong; Lee, Wooyoung; Cho, Seung‐Woo; Lee, Taeyoon
<x xml:space="preserve">Abstract</x> On page 7043, S.‐W. Cho, T. Lee, and co‐workers demonstrate human adipose‐derived stem cell spheroids exhibiting enhanced viability, cell‐cell, and cell‐matrix interaction that can be prepared using a nanowire superhydrophobic surface with on‐and‐off water adhesion switch. The stem cell spheroids produced on this surface exhibit significantly enhanced angiogenic efficacy compared to those grown by conventional methods, which potentiates stem cell therapy. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>